2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--33420
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Empathy in Choosing Majors

Abstract: holds a B.S.E.E. (1986) and M.S.E.E. (1988) degree from the University of Arkansas, and a D.Sc. degree in Electro-physics from the George Washington University (2001). Dr. Jacobs is a licensed professional engineer in the state of Tennessee. Dr. Jacobs began teaching in 2006 after a 17 year career as a US Department of Defense researcher. He currently serves as the Undergraduate Coordinator for the Electrical and Computer Engineering Department of the University of Memphis. He is actively involved in curriculu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…MacDonald and Durdyev [9] found that friends' and family members' influence did not strongly affect female students' propensity to study the civil engineering adjacent fields of "architecture, engineering, and construction studies." Jacobs et al [10] conducted focus groups on women in STEM and engineering disciplines and found that "fathers and math teachers play in the choices women make to study engineering," although this influence affected both students' decisions for and against majoring in engineering.…”
Section: Literature Reviewmentioning
confidence: 99%
“…MacDonald and Durdyev [9] found that friends' and family members' influence did not strongly affect female students' propensity to study the civil engineering adjacent fields of "architecture, engineering, and construction studies." Jacobs et al [10] conducted focus groups on women in STEM and engineering disciplines and found that "fathers and math teachers play in the choices women make to study engineering," although this influence affected both students' decisions for and against majoring in engineering.…”
Section: Literature Reviewmentioning
confidence: 99%